Transmembrane Peptides Influence the Affinity of Sterols for Phospholipid Bilayers - Nyström, Joel H.; Lönnfors, Max; Nyholm, Thomas K.M. (Biophysical journal, 2010)
Cholesterol is distributed unevenly between different cellular membrane compartments, and the cholesterol content increases from the inner bilayers toward the plasma membrane. It has been suggested that this cholesterol gradient is important in the sorting of transmembrane proteins. Cholesterol has also been to shown play an important role in lateral organization of eukaryotic cell membranes. In this study the aim was to determine how transmembrane proteins influence the lateral distribution of cholesterol in phospholipid bilayers. Insight into this can be obtained by studying how cholesterol interacts with bilayer membranes of different composition in the presence of designed peptides that mimic the transmembrane helices of proteins. For this purpose we developed an assay in which the partitioning of the fluorescent cholesterol analog CTL between LUVs and mβCD can be measured. Comparison of how cholesterol and CTL partitioning between mβCD and phospholipid bilayers with different composition suggests that CTL sensed changes in bilayer composition similarly as cholesterol. Therefore, the results obtained with CTL can be used to understand cholesterol distribution in lipid bilayers. The effect of WALP23 on CTL partitioning between DMPC bilayers and mβCD was measured. From the results it was clear that WALP23 increased both the order in the bilayers (as seen from CTL and DPH anisotropy) and the affinity of the sterol for the bilayer in a concentration dependent way. Although WALP23 also increased the order in DLPC and POPC bilayers the effects on CTL partitioning was much smaller with these lipids. This indicates that proteins have the largest effect on sterol interactions with phospholipids that have longer and saturated acyl chains. KALP23 did not significantly affect the acyl chain order in the phospholipid bilayers, and inclusion of KALP23 into DMPC bilayers slightly decreased CTL partitioning into the bilayer. This shows that transmembrane proteins can both decrease and increase the affinity of sterols for the lipid bilayers surrounding proteins. This is likely to affect the sterol distribution within the bilayer and thereby the lateral organization in biomembranes.